2021
DOI: 10.1136/jclinpath-2020-206964
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cellular myocardial infiltration on clinical outcome in non-ischaemic heart failure

Abstract: AimsSo far, little has been known on whether myocardial inflammatory infiltration influences heart failure (HF) progression. Thus, the aim of this study was to test the impact of intramyocardial infiltration on clinical outcomes.MethodsBiopsy samples from 358 patients with stable HF secondary to dilated cardiomyopathy were studied. Immunohistochemistry for lymphocyte (CD3) and macrophage (CD68) markers was performed and counted. After a 1-year follow-up, patients were classified as improved based on the predef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It has generally been assumed that chronic immune response may play an important role in the development and disease progression [2,4]. Accordingly, we recently reported that a higher number of CD68-positive macrophages in biopsy specimens signi cantly predicted clinical progression of HF due to DCM in patients after one-year follow-up [5]. These observations con rmed the previously reported impact of macrophages on the prognosis in DCM [6].…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…It has generally been assumed that chronic immune response may play an important role in the development and disease progression [2,4]. Accordingly, we recently reported that a higher number of CD68-positive macrophages in biopsy specimens signi cantly predicted clinical progression of HF due to DCM in patients after one-year follow-up [5]. These observations con rmed the previously reported impact of macrophages on the prognosis in DCM [6].…”
Section: Introductionsupporting
confidence: 86%
“…the rst was characterized by their presence in the interstitial space, without direct contact with the surrounding cardiomyocytes and the second showed macrophages attached to injured cardiomyocytes using immunohistochemistry. Both of these forms were inversely proportional to cTnT serum levels, which suggested insu cient clearance of phagocytic activity of these cells in DCM patients [5].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation